Influence of imidazole‐based acidity control of PEDOT:PSS on its electrical properties and environmental stability. Issue 15 (5th April 2016) - Cho, Ahra; Kim, Seyul; Kim, Soyeon; Cho, Wonseok; Park, Chanil; Kim, Felix Sunjoo; Kim, Jung Hyun
ABSTRACT: Poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) has been studied for a wide range of applications due to its potential as a transparent electrode. Herein, the use of imidazole and its derivatives as a neutralizing additive for PEDOT:PSS dispersion and in‐depth studies of their effects in terms of electrical properties and stability is reported. Although the neutralization in general reduces the electrical conductivity of PEDOT:PSS, the conductivity after imidazole treatment (685.2 S cm −1 ) is higher than that after treatment of other derivatives. Spectroscopic and thermoelectric studies show that the de‐doping effect resulted in the conductivity reduction. As a trade‐off of the conductivity reduction, greatly enhanced long‐term stability and noncorrosive characteristics are obtained after neutralization. The change in sheet resistance of imidazole‐treated PEDOT:PSS after 500 h under harsh conditions (85 °C and 85% humidity) is half that of the untreated samples, demonstrating the great enhancement of the stability. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1530–1536 Abstract : Poly(3, 4‐ethylenedithiophene):poly(styrenesulfonate) (PEDOT:PSS) has been studied for a wide range of applications due to its potential as a transparent electrode. However, post‐treatment of PEDOT:PSS is necessary for electronic applications due to the poor electrical stability. In this study, the neutralization process of PEDOT:PSS solutions is investigated by using imidazole and imidazole derivatives as a weak base to obtain highly conductive and stable PEDOT:PSS.